In vivo evaluation of the inflammatory response and IL-6 immunoexpression promoted by Biodentine and MTA Angelus - Fonseca, T. S. da [UNESP]; Silva, G. F. da [UNESP]; Tanomaru Filho, Mario [UNESP]; Sasso-Cerri, E. [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Cerri, Paulo Sérgio [UNESP] (Wiley, 2015)
Aim To evaluate the inflammatory process induced by Biodentine and mineral trioxide aggregate (MTA) in rat subcutaneous tissues. Methodology A polyethylene tube filled with Biodentine (n = 20) or MTA (n = 20) was placed into the dorsal subcutaneous of forty male rats; in the control group (CG; n = 20), empty tubes were implanted. After 7, 15, 30 and 60 days, the polyethylene tubes surrounded by connective tissue were fixed and embedded in paraffin. The number of inflammatory cells was estimated in HE-stained sections; numerical density of interleukin-6 (IL-6)-immunolabelled cells was also performed. The differences amongst the groups were analysed statistically by Tukey's test (P ≤ 0.05). Results A high number of inflammatory cells and IL-6-positive cells were observed at 7 days, in all groups; however, in the Biodentine group, the number of inflammatory cells and IL-6-immunolabelled cells was significantly higher (P ≤ 0.05) in comparison with the other groups at 7 and 15 days. In the capsules of animals from all groups, a gradual and significant reduction (P ≤ 0.05) of these parameters was seen over time. At 60 days, the capsules exhibited numerous fibroblasts and bundles of collagen fibres; in addition, the number of IL-6-positive cells was not significantly different amongst Biodentine, MTA and control groups. Conclusions There was a significant regression in the inflammatory reaction in the capsules indicating, therefore, that Biodentine is a biocompatible material.
Keywords: Biocompatibility; Biodentine; Immunohistochemistry; Interleukin-6; MTA Angelus